Correlation Between Parental Verbal Violence and Adolescents’ Self-Confidence in Junior High School Students - Fadlia, Khafidhotul; Insiyah, Insiyah; Caturini, Endang (Poltekkes Kemenkes Surakarta, 2023)
Background: Parents should provide the best upbringing for their children, but sometimes the majority of parents educate their children with violence. Verbal violence is insulting, yelling, and saying inappropriate words. This study analyses the relationship between parental verbal violence and adolescents' self-confidence. Methods: Quantitative design with an approach to 264 respondents with simple random sampling technique, using a questionnaire measuring instrument. Results: The results of the Kendall's tau-b correlation test obtained a p value of 0.002 with a correlation coefficient of 0.133 in the very low category. Children who experience mild verbal violence (72%) and moderate self-confidence (65.2%). Conclusion: There is a significant relationship between parental verbal violence and adolescents' self-confidence. Parents should be provided with parenting education programs that emphasize positive communication strategies to prevent verbal violence and support the development of adolescent self-confidence.